Polyacetylene glucosides from the florets of Carthamus tinctorius and their anti-inflammatory activity. (July 2021) - Li, Xin-Rui; Liu, Juan; Peng, Cheng; Zhou, Qin-Mei; Liu, Fei; Guo, Li; Xiong, Liang
Abstract: Five previously undescribed polyacetylene glucosides, namely, four C10 - and one C14 -acetylenes, together with three known analogues, were isolated from the florets of Carthamus tinctorius L. The structures of these novel compounds were elucidated to be (5 R )-5-acetoxy-8, 10, 12-tetradecatriyne-1- O - β -D-glucopyranoside, (2 Z )-decaene-4, 6, 8-triyne-1- O-β- D-glucopyranoside, (8 Z )-1-[(3- O - β -D - glucosyl)-isovaleroyloxy]-8-decaene-4, 6-diyne, (8 Z )-decaene-1-isovaleroyloxy-4, 6-diyne-10- O - β -D-glucopyranoside, and (2 E, 8 E )-decadiene-4, 6-diyne-1- O - β -D-glucopyranoside via spectroscopic and chemical methods. All of the isolated compounds were tested for cytotoxicity against cancer cell lines, antibacterial activity, and inhibitory effects on the lipopolysaccharide (LPS)-induced nitric oxide (NO) production. The results showed that (5 R )-5-acetoxy-8, 10, 12-tetradecatriyne-1- O - β -D-glucopyranoside significantly inhibited LPS-induced NO production in RAW264.7 cells in a dose-dependent manner. Graphical abstract: Image 1 Highlights: Five new polyacetylene glucosides were isolated from Carthamus tinctorius. The cytotoxic, antibacterial, and anti-inflammatory effects of the isolates were evaluated. Compound 1 significantly inhibited LPS-induced NO production in RAW264.7 cells.